2022
DOI: 10.32859/era.23.5.1-31
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ethnomedicinal study of indigenous knowledge on medicinal plants used by the tribal communities of Central Kurram, Khyber Pakhtunkhwa, Pakistan

Abstract: Background: The use of plants for different ethnobotanical purposes is a common practice in the remote areas of developing countries, particularly in reference to human and animal healthcare. For this aim, it is important to document ethnomedicinal use of plants for human and livestock healthcare from unexplored regions.Objective: The current study aimed to document the use of medicinal plants and to assess their conservation status.We hypothesized that Central Kurram, due to its remoteness and maintenance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
5
35
0
Order By: Relevance
“…A large number of therapeutic plants have been previously reported from adjacent tribal areas. 7 5 5 4 4 4 3 2 1 1 1 1 1 1 1 1 1 Tariq et al 2015;Hussain et al 2022;Irfan et al 2018a, b, c). Indigenous people used all plant parts in drug preparation, but leaves were used most commonly in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of therapeutic plants have been previously reported from adjacent tribal areas. 7 5 5 4 4 4 3 2 1 1 1 1 1 1 1 1 1 Tariq et al 2015;Hussain et al 2022;Irfan et al 2018a, b, c). Indigenous people used all plant parts in drug preparation, but leaves were used most commonly in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mentha longifolia, Medicago sativa and Morus alba had the highest (0.7) UV value (Table 1, Figure 5). (Haq & Badshah 2021, Hussain et al 2022. The people of the study area have maintained the traditional lifestyles depending on wild and cultivated plants for food, fuel, fodder, construction material and crude drugs.…”
Section: Use Value (Uv)mentioning
confidence: 99%
“…Several previous studies show similar results that 39.9%-72.64% of respondents use herbaceous plants as traditional medicines both in Indonesia and in other countries (Amsalu et al 2018;Ali et al 2020;Hu et al 2020;Kidane et al 2018;Hussain et al 2022). This is likely because the search and mode of use of this plant group are easy besides the therapeutic indication of its medicinal properties (Baydoun et al 2015;Bahadura et al 2020).…”
Section: Growth Form and Plant Parts Usedmentioning
confidence: 63%
“…Asteraceae and Lamiaceae contributed the most medicinal species, with 8 species each (Figure 2), followed by Euphorbiaceae with 5 species, Fabaceae and Poaceae with 4 species each, Acanthaceae, Burseraceae, Cyperaceae, and Myrtaceae with 3 species each, and the remaining families each with one or two species. Another study found that Asteraceae and Lamiaceae were the dominant families with 5-15 medicinal plant species in South Aceh (Suwardi et al 2021), Malaysia (Ramli et al 2021), Pakistan (Hussain et al 2022), Southwest Algeria (Bouafia et al 2021), and Ethiopia (Bahadura et al 2020;Chekole et al 2015;Getaneh and Girma 2014;Meragiaw et al 2016).…”
Section: Diversity Of Wild Edible Fruit Plants and Their Usesmentioning
confidence: 99%